Visual evoked potentials in infants exposed to methadone in utero. Issue 9 (27th February 2008) - McGlone, L; Mactier, H; Hamilton, R; Bradnam, M S; Boulton, R; Borland, W; Hepburn, M; McCulloch, D L
Abstract : We investigated the effects of maternal drug misuse on neonatal visual evoked potentials (VEPs). Flash VEPs were recorded within 4 days of birth from 21 term infants of mothers misusing drugs and prescribed substitute methadone and 20 controls. Waveforms were classified as typical, atypical, immature or non-detectable, and amplitude and latencies were measured. VEPs from drug-exposed infants were less likely to be of typical waveform and more likely to be immature or non-detectable (p<0.01) than those of control infants. They were also smaller in amplitude (median 10.8 vs 24.4 μV, p<0.001). VEPs of drug-exposed infants had matured after 1 week but remained of lower amplitude than VEPs of newborn controls (p<0.01) and were non-detectable in 15%. Flash VEPs differ between maternal drug-exposed and non-drug-exposed newborns. Future research should address the specific effects of maternal methadone and/or other illicit drug misuse on infant VEPs, and associations between neonatal VEPs and subsequent visual development.